The improvement of emergencies from health training: A view of interim resident physicians - Lafuente, Jorge Carlos; González-Raboso, Aida (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
This article analyzes the perceptions of five first-year medical residents regarding the relationship between training in health education and the saturation of emergency services. A qualitative methodology has been used in which the individual interview was used as a data collection instrument. The results showed that the doctors pointed out how the users have little knowledge about health care, nor about the operation of the emergency service, the information channels are unreliable (television and internet), which has repercussions in a greater saturation in the Emergencies.